Identification of dual positive CD19+/CD3+ T cells in a leukapheresis product undergoing CAR transduction: a case report - Crystal Mackall; Alice Bertaina; Steven Feldman; Christina Baggott; Bita Sahaf; Kara Lynn Davis; Liora Schultz; Courtney Erickson; Sneha Ramakrishna; Jean Oak; Robbie G Majzner; Shabnum Patel; et al. (Journal for ImmunoTherapy of Cancer)
Background Chimeric antigen receptor (CAR) therapy and hematopoietic stem cell transplantation (HSCT) are therapeutics for relapsed acute lymphocytic leukemia (ALL) that are increasingly being used in tandem. We identified a non-physiologic CD19+/CD3+ T-cell population in the leukapheresis product of a patient undergoing CAR T-cell manufacturing who previously received a haploidentical HSCT, followed by infusion of a genetically engineered T-cell addback product. We confirm and report the origin of these CD19+/CD3+ T cells that have not previously been described in context of CAR T-cell manufacturing. We additionally interrogate the fate of these CD19-expressing cells as they undergo transduction to express CD19-specific CARs.Main body We describe the case of a preteen male with multiply relapsed B-ALL who was treated with sequential cellular therapies. He received an αβ T-cell depleted haploidentical HSCT followed by addback of donor-derived T cells genetically modified with a suicide gene for iCaspase9 and truncated CD19 for cell tracking (RivoCel). He relapsed 6 months following HSCT and underwent leukapheresis and CAR T-cell manufacturing. During manufacturing, we identified an aberrant T-cell population dually expressing CD19 and CD3. We hypothesized that these cells were RivoCel cells and confirmed using flow cytometry and PCR that the identified cells were in fact RivoCel cells and were eliminated with iCaspase9 activation. We additionally tracked these cells through CD19-specific CAR transduction and notably did not detect T cells dually positive for CD19 and CD19-directed CARs. The most likely rationale for this is in vitro fratricide of the CD19+ ‘artificial’ T-cell population by the CD19-specific CAR+ T cells in culture.Conclusions We report the identification of CD19+/CD3+ cells in an apheresis product undergoing CAR transduction derived from a patient previously treated with a haploidentical transplant followed by RivoCel addback. We aim to bring attention to this cell phenotype that may be recognized with greater frequency as CAR therapy and engineered αβhaplo-HSCT are increasingly coupled. We additionally suggest consideration towards using alternative markers to CD19 as a synthetic identifier for post-transplant addback products, as CD19-expression on effector T cells may complicate subsequent treatment using CD19-directed therapy.